Advances in the production of small ruminants in northeastern Mexico - Zapata Campos, Cecilia Carmela; Universidad Autónoma de Tamaulipas (Libros UAT, 2019)
Mexico is a country with a great variety of ecosystems and a great biological diversity, its heterogeneity is reflected in the fauna, flora, climate, orography, and in the diverse economic activities that its population develops in the different ecosystems. Its territory is made up of arid and semi-arid zones. 52% of the total area of ??its territory has less than 400 millimeters of annual average rainfall; The majority of the population that lives in this area lives in extreme poverty, with high levels of marginalization, where productive activities take place, among which caprinoculture stands out.Goats are a species that because of its rusticity and good production have managed to adapt to inhospitable places, difficult to access and with water and forage limitations; This activity has been able to support the inhabitants of the arid areas for decades, by producing milk and meat, but still the producers have not managed to transcend to better living standards. Among the different problems are the structural and idiosyncrasy of the producers. Goat producers have been supported with programs to develop their activity, however, they are of assistance, so it is necessary to implement programs that involve a strategy of business and productive development to make this activity more competitive.